Long-Range Dependence: Ten Years of Internet Traffic Modeling - Karagiannis, Thomas; Molle, Mart; Faloutsos, Michalis (IEEE Internet Computing, 2004)
Self-similarity and scaling phenomena have dominated Internet traffic analysis for the past decade.With the identification of long-range dependence (LRD) in network traffic, the research community has undergone a mental shift from Poisson and memory-less processes to LRD and bursty processes. Despite its widespread use, though, LRD analysis is hindered by our difficulty in actually identifying dependence and estimating its parameters unambiguously.The authors outline LRD findings in network traffic and explore the current lack of accuracy and robustness in LRD estimation. In addition, the authors present recent evidence that packet arrivals appear to be in agreement with the Poisson assumption in the Internet core.